Climatic Impacts on Drug Therapy Usage: A Comparative Study of Kurdish Populations in Sulaimani, Iraq, and Stockholm, Sweden - Shena Ali Faris; Pakiza Aziz Saied (UHD Journal of Science and Technology)
The geographical area is influenced by climate impacts, which, in turn, affect the use of different drug therapies during seasonal weather fluctuations. Thus, this study investigates how geographical climate differences influence drug therapy usage by comparing two Kurdish populations residing in Sulaimani, Iraq, and Stockholm, Sweden. It also highlights significant variations in healthcare practices, demonstrating how environmental conditions shape medication patterns. Data collection was conducted through a structured online survey, covering sociodemographic factors, health behaviors, and medication practices, followed by statistical analysis using Python and SPSS. Geographic Information System (GIS) tools were applied to spatially analyze environmental variables across the two cities, enabling the validation of sampling locations and the statistical determination of optimal limitations for the sample collection dataset. In Stockholm, 73.33% of respondents reported that the cold and humid climate affected their health behavior, whereas in Sulaimani, 50.27% described the climate as moderate but highly variable. The study revealed that the key statistical values such as antibiotic usage were significantly higher in Sulaimani (38.03%) than Stockholm (14.00%, P < 0.001), indicating a more treatment-focused approach in Sulaimani versus a preventive focus in Stockholm. Similarly, painkiller usage was significantly higher in Sulaimani, correlating with climate-related seasonal illnesses. Meanwhile, multivitamin usage in Stockholm reached 44.67%, surpassing Sulaimani’s 37.77%, reflecting a stronger emphasis on preventive healthcare strategies in colder climates. These findings emphasize that climate, more than cultural differences, significantly influences drug therapy patterns. The study determines that healthcare strategies should integrate climate variability, prioritizing preventive care in colder climates and infection control in warmer regions. Finally, the study concludes with key findings and outlines directions for future research, emphasizing the need for further investigation into climate-adaptive healthcare approaches.